Multiple unerupted teeth – an interesting challenge. (2nd October 2019) - Adam, Naeem; Flett, Andrew; Sandler, Cara
Abstract : This paper describes primary failure of eruption and presents some of the theories about the aetiology of this clinical condition. It also covers single ankylosed teeth as well as cases that present with multiple unerupted teeth. The various approaches to the clinical management of this not uncommon problem are discussed, along with the pros and cons of some of these techniques. One difficult clinical challenge is documented, where a 14-year-old patient presented with 19 unerupted permanent teeth and, with the help of rare-earth magnets and upper and lower fixed appliances, within a two-year period a good result was achieved. CPD/Clinical Relevance: Clinicians encounter teeth that have failed to erupt on a regular basis. Appropriate diagnosis and treatment planning of these cases, and subsequent effective clinical management, is imperative to ensure the most favourable outcome for our patients.